Perbedaan Pengaruh Latihan Konsentrasi Dan Latihan Koordinasi Terhadap Peningkatan Kemampuan Shooting Game Atlet Petanque Undikma - Lubis, Muhammad Ridwan; Permadi, Andi Gilang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This research is motivated by the inconsistency of the shooting ability of athletes in shooting games in Petanque sports, both at the regional and national levels. This study aims to determine the effect of concentration training and coordination training on the improvement of the shooting game ability of Undikma petanque athletes. This study used an experimental method with the design of "two group pretest posttest design". The research instrument used was a shooting ability test with shooting stations 1, 2, 3, 4, and 5 with a distance of 6 meters, 7 meters, 8 meters, and 9 meters. The sample in this study were 14 Undikma Petanque athletes. Sampling using purposive sampling technique. Based on the results of the t-test analysis showed the same significant results between concentration training and coordination training. However, the result of the concentration exercise was better than the coordination exercise. It was seen that the average value of shooting using the pretest result of concentration training was 4.71 which increased by 13.00. The amount of increase was 8.28. The coordination exercise, which was originally the pretest average result of 3.42 increased to 10.00. The amount of increase was 6.57. The difference in the average result of shooting game improvement with concentration training and coordination training is 1.71.